12+.60x=.40(60+x)

Simple and best practice solution for 12+.60x=.40(60+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+.60x=.40(60+x) equation:


Simplifying
12 + 0.60x = 0.40(60 + x)
12 + 0.60x = (60 * 0.40 + x * 0.40)
12 + 0.60x = (24 + 0.40x)

Solving
12 + 0.60x = 24 + 0.40x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.40x' to each side of the equation.
12 + 0.60x + -0.40x = 24 + 0.40x + -0.40x

Combine like terms: 0.60x + -0.40x = 0.2x
12 + 0.2x = 24 + 0.40x + -0.40x

Combine like terms: 0.40x + -0.40x = 0.00
12 + 0.2x = 24 + 0.00
12 + 0.2x = 24

Add '-12' to each side of the equation.
12 + -12 + 0.2x = 24 + -12

Combine like terms: 12 + -12 = 0
0 + 0.2x = 24 + -12
0.2x = 24 + -12

Combine like terms: 24 + -12 = 12
0.2x = 12

Divide each side by '0.2'.
x = 60

Simplifying
x = 60

See similar equations:

| 6(2-8n)=5y-36 | | R7/R12 | | (2-4/7)/ | | y=-3(-3)-1 | | 1=-r-4 | | m/15-7=-8 | | -2(8+3n)=-28-8n | | 18+.60x=.40(60+x) | | 4t^3+3t^2= | | x^2-690x=1248 | | -(-2x+2)=7y+-14 | | 12v+8v= | | -6(10+n)=-156 | | t^3+t^2+t= | | 2/3(x-9)=12 | | 1.45x+y=1.1 | | -9-6x=63 | | 18+.40x=.60(60+x) | | 2m+10=7 | | Inx=5-x | | 272/210 | | t^3+343= | | x+7x-12=14-3x+1 | | 27x^2y^3+x^3y= | | -4(k-10)=-28 | | u/6{{^7/9}} | | TC=20+4Q | | 144-81x^2= | | b-7/14=-1 | | x^2-53x=144 | | -40=5(x+9) | | r/8-9=-10 |

Equations solver categories